Typescript copies of witness statements (L) taken by Florence O'Donoghue for the Bureau of Military History and relating to events in Cork City and County - Bureau of Military History, 1913-1921; O'Donoghue, Florence, 1895-1967; Lynch, Diarmuid, 1878-1950 (1947)
Statements by Robert Langford, Michael Leahy, Patrick Looney, Denis Lordan, Harry Lorton, Diarmuid Lynch, Eamonn Lynch, Michael P. Lynch and Denis Lyons.
Keywords: Irish Republican Army; Ireland -- History -- 1922-